SISTEMA AUTOMATIZADO PARA LA ADMINISTRACIÒN Y CONTROL DE PRODUCCIÓN DE LAS CAJAS DE BANANO DE LA HACIENDA CLEMENTINA “COOPROCLEM” - QUIÑONEZ PALMA, MILTON RENE (2019)
Currently, companies at the national and international level seek to automate their processes or activities, due to the fact that technology is being integrated in most companies, without exception the Clementina ranch being one of the largest in Ecuador, and having As a main activity the production and export of bananas, which is done manually, in this way we have visualized that one of the parts that can be automated is the weighing of banana boxes, since from this point the need arises to calculate and record some data such as production and performance. The purpose of the system is to innovate the processes carried out in the offices of each baler and to automate the counting and weighing of the banana boxes, to have greater security in the data, availability and order of the information, which will be registered in a warehouse MySQL data, for this reason there are many free or free development platforms to create systems, in order to lower costs and increase profits. The system is developed under the line of research development of information systems, communication and business and technological enterprises, and in the subline of research of intelligent automation of industrial processes, in summary, is the general guide of development of the prototype following an order and consecutive process in the creation of the SAACCB system to perform the analysis of the necessary requirements for the system, the observation technique was used and as an instrument the interview that are part of the qualitative research methodology